We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
47
1
avatar

If \(a \star b = \dfrac{\left(\dfrac{1}{b} - \dfrac{1}{a}\right)}{(a - b)}\), express \(3 \star 11\) as a common fraction.

 Oct 30, 2019
 #1
avatar+104932 
+1

a *  b  = 3 * 11  =

 

(1/11 - 1/3)

_________   =

  3   -  11

 

 (  3 - 11)  / (11*3)

   ____________   =

   (3 - 11)  / 1

 

 

(3 - 11) / (11*3)   *   ( 1) /  (3 - 11)  =

 

   1

____  =

11*3

 

 1

__

33

 

 

cool cool cool

 Oct 30, 2019

33 Online Users